Reliability and Validity of Physical Tools and Measurement Methods to Quantify Hand Swelling: A Systematic Review. Issue 2 (12th December 2020) - Llanos, Catalina; Gan, Ellen Yanxiang; Chen, Jophie; Lee, Mi-Joung; Kilbreath, Sharon L; Dylke, Elizabeth S
Abstract: Objective: Hand swelling may result from injury or trauma. Various physical assessment tools and measurement methods can be used to quantify the volume or size of the hand or fingers; however, the reliability and validity of each tool and measurement method have not been evaluated. The purpose of this study was to evaluate the reliability and validity of physical assessment tools and methods used to quantify hand and finger volume orsize. Methods: MEDLINE, CINAHL, EMBASE, Web of Science, and Scopus were searched using key terms related to swelling, edema, volume, size, hand, measures, reliability, and validity. Cross-sectional or longitudinal studies that assessed reliability and/or validity of physical assessment tools or measurement methods to quantify hand swelling were included. Two examiners independently extracted data from the included articles and appraised the articles' quality using the Consensus-Based Standards for the Selection of Health Measurement Instruments methodology. Data extracted from studies analyzing reliability and validity were grouped by type of assessment tool and measurement method. Results: Five physical assessment tools used for quantification of hand swelling were evaluated, including tape measure, water volumeter, bioimpedance spectroscopy, ring gauge, 3-dimensional techniques. All assessment tools had good to excellent reliability (ICC = 0.74 − 0.99), and moderate to high validity (Pearson coefficient = 0.58 − 0.99), for quantification of the volume or size of the hand or fingers. Conclusion: All measurement methods with these tools had good to excellent reliability and moderate to high validity. The evidence underpinning the figure-of-eight technique, which uses a tape measure, was the highest. Because these physical assessment tools and measurement methods assess different aspects and regions of the hand, which one is selected depends on the region of interest for assessment and the availability of tools. Impact: Reliable tools and measurement methods are available to measure the size or volume of the hand and fingers, either together or separately. The best tool will depend on the aim of assessment and tool availability. Lay Summary: Hand swelling can occur with injuries, burns, or lymphedema. This review shows that tools are available to accurately measure swelling in any part of thehand.